1991
DOI: 10.1136/bmj.303.6809.1023
|View full text |Cite
|
Sign up to set email alerts
|

Community care for patients with schizophrenia one year after hospital discharge.

Abstract: Objectives-To document the circumstances and care of patients with schizophrenia who had recently been discharged from local psychiatric inpatient services, and to establish the extent to which misgivings about community care might be justified.Design Main outcome measures-Diagnosis elicited by present state examination, global social disability rating, use of services during the three months before interview.Results-89 of the 140 patients (64%) had been ill for five or more years, yet few were former long sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(51 citation statements)
references
References 15 publications
2
48
0
1
Order By: Relevance
“…1-4 Melzer et al, 26 in a 1-year follow-up study of schizophrenic patients discharged from psychiatric hospitals in London, found that at follow-up 29% of the sample had good or excellent social adjustment, 50% had fair or poor, and 22% had very poor social adjustment or severe disability. Four years later, 41% were in the intermediate group, 41% showed good levels of social adjustment, and 18% had severe disabilities.…”
Section: Interpretation Of Resultsmentioning
confidence: 99%
“…1-4 Melzer et al, 26 in a 1-year follow-up study of schizophrenic patients discharged from psychiatric hospitals in London, found that at follow-up 29% of the sample had good or excellent social adjustment, 50% had fair or poor, and 22% had very poor social adjustment or severe disability. Four years later, 41% were in the intermediate group, 41% showed good levels of social adjustment, and 18% had severe disabilities.…”
Section: Interpretation Of Resultsmentioning
confidence: 99%
“…Patients reported positive attitudes toward short hospitalizations and community resources, citing beneficial gains from treatment, activities, staff interaction, a safe environment, improved insight into their condition, and opportunities for selfimprovement. In contrast, other patients reported that the available community resources and services were of such low quality, they were better off not using them (Melzer et al [15]). …”
Section: Paradigm Shift 2: 1976-1995mentioning
confidence: 94%
“…Associating the symptoms with a learned behavior, however, increased patient active participation in learning about behavioral adjustment. The patient had an active role in the future, rather being a Gruenberg et al [12] and Melzer et al [15] discussed individualized care. Chronic patients, especially those with highest need, underused the available community resources.…”
Section: Paradigm Shift 2: 1976-1995mentioning
confidence: 99%
See 1 more Smart Citation
“…2 4 They also tend to experience obstacles accessing community care services following discharge from hospital 5 and have particular difficulties with re-integration into society. 6 These problems are compounded by fact that lower socio-economic group is associated not only with increased rates of mental illness 79 but also with younger age at presentation 10 and longer durations of untreated illness" -clinical features which are strongly associated with more severe forms of illness 18 and poorer outcomes.…”
mentioning
confidence: 99%